Establishment of shari’ah supervisory committee in hospital: an analysis from perspective of public interest - Samsudin, Muhammad Adib; Yahaya, Mohammad Zaini; Mohd Kashim, Mohd Izhar Ariff; Laluddin, Hayatullah; Mohd Sobri, Irwan; Ismail, Ahmad Munawar; Mohd Khalid, Rozida; Syed Sulaiman, Syed Azhar (Canadian Center of Science and Education, 2015)
Although hospitals’ management currently observe all general rules set by the government nevertheless, there are certain short comings on the part of management, as it lacks comliance with the requirement of Shari’ah in respects of selection of medicine, the relations between the patients and the doctors of differnt gender, and the lack of the knowledge of Shari’ah’s ruling pertainning to the treatment by staffs and the patients in the hospital. These three aspects should be given serious attention and be handled wisely so as to maintain and preserve Malaysia’s status as a majority Muslim country. As regards the selection of the medicine or pharmaceutical material, there is a lingerring doubt concerning the status of the medicine given to patient whether it is halal (permissible) or haram (impermissible). For instance, the medicine for allergy Red Tab Claritin and Ultratab Allergy Tablet Benadryl contain materials that originate from pig and cow. Meanwhile, there are numerous complaints from female patients especially, during labour hours in the delivery hall handaled by male doctors. Some of them don’t feel easy and confortable with the birth procedure being conducted by male doctors. Therefore, to cater for the need of the Muslim community constituting the majority of Malaysia’s population, it is appropriate to establish a committee tasked with making sure that the hospitals operate in accordance with the requirement of the Shari’ah. Therefore, this paper attempts to explore the concept of maslahah from the perspective of Islamic law and its instrumental role in the establishment of Shari’ah Supervisory Committee in hospitals. This paper uses both document analysis and interview methods. The findings of this study show that maslahah can play an instrumental role in establishing Shari’ah Supervisory Committee in the hospital from the aspects of enhancement of general public interest of necessity category.